Kesetaraan Gender dalam Al-Qur'an (Studi atas Pemikiran Hamka terkait Kewarisan) - Ainun Hakiemah; Farida Nur Afifah; Siti Muliana (Refleksi: Jurnal Kajian Agama dan Filsafat, 2021)
The focus of this paper study is related to inheritance in Hamka's perspective. The topic of the author considers important because there are still lack of studies on the themes of gender equality based on the perspective of certain figures. So that the author's expectations with this paper can open up and add to the treasures related to gender equality, especially in terms of inheritance. The determination of this topic aims to respond to the present reality, where some people or groups that make the Quran verses relate to inheritance as a legitimacy of the division of inheritance that does not draw to women without seeing the side Historical verses are derived. Reviewing the historical socio-based method is used in this paper. The conclusion in this paper is that the opinion of Hamka regarding the inheritance of the quarter in line with the opinion of Muhammad Abduh and his disciple Rasheed Ridha that suggests that men get a lot more because of the burden of ownership of the property more Weight than women. But it can change, in line with the development of community context. Hamka's opinion defies strongly against the opinion of classical mufasirs that argue that women lack common sense, property extravagant property and other gender biased opinions that cause the division of its birthright to be denied.